Somatic Symptoms among Children and Adolescents in Poland: A Confirmatory Factor Analytic Study of the Children Somatization Inventory - Essau, Cecilia; Olaya, Beatriz; Bokszczanin, Anna; Gilvarry, Catherine; Bray, Diane (Frontiers in Public Health, 2013)
The aim of the present study was to examine the factor structure and psychometric properties of the short version of the Children’s Somatization Inventory (CSI-24) in Poland. The CSI-24 is a self-report questionnaire designed to assess somatic symptoms in children and adolescents. A total of 733 children and adolescents, aged 12 to 17 years, participated in this research. The participants for this study were recruited from urban and suburban schools of Opole province in South Western Poland. In addition to the CSI-24, all participants completed the Spence Children’s Anxiety Scale (SCAS) and the Strength and Difficulties Questionnaire (SDQ). The bifactor model that included the three domain-specific factors (i.e., gastro, pseudoneurological and pain/weakness) showed better fit indices than the three-factor model. Goodness-of-fit of the bifactor model with the four domain-specific factors was poorer than the four correlated factors. The Cronbach’s Alpha for the CSI-24 was .91. Somatic symptoms correlated significantly highly with the SCAS total scores and the SDQ emotional subscale, suggesting good construct validity. Somatic symptoms had low correlation with the SDQ behavioral problems symptoms, suggesting adequate discriminant validity. The CSI-24 reliably measured somatic symptoms in children and adolescents in Poland.